Magnetic Spinels - Synthesis, Properties and Applications 2017
DOI: 10.5772/66293
|View full text |Cite
|
Sign up to set email alerts
|

Spinel‐Structured Nanoparticles for Magnetic and Mechanical Applications

Abstract: Nanoparticles of Fe 3 O 4 have been successfully synthesized using a simple coprecipitation technique from natural iron sands, employing HNO 3 and NH 4 OH as dispersing and precipitating agents, respectively. The substitution of Fe with Mn to result in Fe 3x Mn x O 4 (0 ≤ x ≤ 3) was conducted to control the magnetic strength of this nano-sized spinel powder. It is shown that magnetic properties depend not only on the particle size and Mn doping but also on the particles clustering. The applications for magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Fe 3 O 4 ferrofluids or magnetic colloids are composed of single-domain magnetite particles dispersing in an appropriate liquid carrier [25]. Previous papers showed that ferrofluids tend to be unstable fluids due to agglomeration phenomena [26][27][28].…”
Section: Introduction mentioning
confidence: 99%
“…Fe 3 O 4 ferrofluids or magnetic colloids are composed of single-domain magnetite particles dispersing in an appropriate liquid carrier [25]. Previous papers showed that ferrofluids tend to be unstable fluids due to agglomeration phenomena [26][27][28].…”
Section: Introduction mentioning
confidence: 99%